Potentiality on e-commerce in the rural community of Bangladesh - Islam, F; Kazal, MMH; Rahman, MH (Progressive Agriculture, 2016)
Bangladesh is a least developed country where a large number of population in rural areas live under substantial poverty. Recently, a phenomenal growth has witnessed in accessing mobile phone and internet which showing a new way for trade and commerce (e-commerce). But it is a big challenge to establish and provide the facilities of e-commerce to the majority population live in rural areas. This study explores the potential role of e-commerce in promoting sustainable and equitable development in rural areas. We discuss the possibilities of using e-commerce technology in a way that will benefit the rural communities. The growth of mobile and internet users, the digital divide between rural and urban population, problems related with dispersing the service of e-commerce in rural areas and future prospects are presented. There are a number of challenges but however, recently introduced community e-centers has a good potential which can provide the services of e-commerce in rural areas. In addition, to support low-income rural population, there is a need for governmental funding for expansion and development of rural infrastructure. This study might be helpful for the policy makers to implement the appropriate development strategy for reducing poverty and betterment of living standard in rural areas. Progressive Agriculture 27 (2): 207-215, 2016